How science enhanced animation / Azahar Harun - Harun, Azahar (Faculty of Art and Design, Universiti Teknologi MARA Melaka, Alor Gajah Campus, 2014)
Science is essential to an animation as brick is to a building. In fact, some of the early works of animation started as a science project rather than a work of art. According to Wells (2001), in the early stage, scientists and innovators were keen on developing media platform rather than furnishing the animation content with narrative and character style. For instance, the the aumatrope is recognised as a the device used by Dr John Aryton Paris to demonstrate a phenomenon called "Persitence of vision" to the British Royal College of Physcians in 1827 (Zell-Ravenheart, 2006) . The device has a single card disc with two pieces of strings attached to it . Each side of the card disc has different figures. To operate Thaumatrope, one need to twist the disc for several times until the strings get tighten and then pull them away to make it spin. As this happen, the two figures from each side of the card disc will merge as one. Thaumatrope is just one of many optical devices that has inspire many scientists and animation artists. In this essay, I will discuss how science can help enhance the understanding of animation.